Prone restraint cardiac arrest: A comprehensive review of the scientific literature and an explanation of the physiology. (July 2021) - Steinberg, Alon
Deaths occurring among agitated or violent individuals subjected to physical restraint have been attributed to positional asphyxia. Restraint in the prone position has been shown to alter respiratory and cardiac physiology, although this is thought not to be to the degree that would cause asphyxia in a healthy, adult individual. This comprehensive review identifies and summarizes the current scientific literature on prone position and restraint, including experiments that assess physiology on individuals restrained in a prone position. Some of these experimental approaches have attempted to replicate situations in which prone restraint would be used. Overall, most findings revealed that individuals subjected to physical prone restraint experienced a decrease in ventilation and/or cardiac output (CO) in prone restraint. Metabolic acidosis is noted with increased physical activity, in restraint-associated cardiac arrest and simulated encounters. A decrease in ventilation and CO can significantly worsen acidosis and hemodynamics. Given these findings, deaths associated with prone physical restraint are not the direct result of asphyxia but are due to cardiac arrest secondary to metabolic acidosis compounded by inadequate ventilation and reduced CO. As such, the cause of death in these circumstances would be more aptly referred to as "prone restraint cardiac arrest" as opposed to "restraint asphyxia" or "positional asphyxia."